THE EFFECTS OF THE COMBINED FORMULA OF SI JUN ZI TANG AND WU BEI SAN IN TREATING DUODENITIS A MODERN TRADITIONAL MEDICINE PERSPECTIVE (Vietnam Journal of Community Medicine, 2026)
Objectives: To evaluate the therapeutic efficacy of the combined formula Si Jun Zi Tang and Wu Bei San in the treatment of Helicobacter pylori negative gastroduodenitis corresponding to the spleen-stomach deficiency cold pattern of epigastric pain syndrome in traditional medicine, and to analyze the mechanisms of action of the formula from the perspectives of modern pharmacology and traditional medicine pattern differentiation.Subjects and methods: A prospective controlled study was conducted on patients with H.pylori negative gastroduodenitis classified as the spleen-stomach deficiency cold pattern of epigastric pain syndrome according to traditional medicine. The treatment group received the combined formula Si Jun Zi Tang and Wu Bei San, while the control group was treated with Pantoprazole. The treatment duration was 28 days. Outcome measures included the severity of epigastric pain, abdominal distension, belching and acid regurgitation, and loose stools. Comparisons were performed before and after treatment and between the two study groups.Results: After 28 days of treatment, the group receiving the combined formula showed significant improvement in clinical symptoms compared with baseline (p < 0.05). The prevalence of epigastric pain decreased from 100% to 26.7%; abdominal distension from 73.3% to 28.9%; belching and acid regurgitation from 75.6% to 35.6%; and loose stools from 80% to 15.6%. The improvement in symptoms in the treatment group was statistically superior to that in the Pantoprazole-treated control group (p < 0.05).Conclusion: The combined formula Si Jun Zi Tang and Wu Bei San is more effective than Pantoprazole in improving common symptoms in patients with gastritis and duodenitis. Its therapeutic efficacy is supported by clinical evidence and is consistent with modern pharmacological findings as well as the traditional medicine principles of pattern differentiation and formula composition, confirming the scientific basis and clinical applicability of the formula.
Keywords: Combined formula, Si Jun Zi Tang, Wu Bei San, gastroduodenitis, epigastric pain syndrome.